Optimization of obtaining the high label single strain probe based on the M13 phage - Telegeev, G.D.; Dybkov, M.V.; Kiyanitsa, K.N. (Биополимеры и клетка, 1995)
A method is proposed to obtain high-label single strain probe on the basis of the M13 phage. This is based on the use of a specific primer and the procedure of purification of the synthesized probe using nitrocellulose. Наведено методику одержання високоміченого одноланцюгового зонда на основі фага М13, що базується на використанні специфічного праймеру та процедурі очищення синтезованого зонду за допомогою нітроцелюлози. Приведена методика получения высокомеченного одноцепочечного зонда на основе фага М13, базирующаяся на использовании специфического праймера и процедуре очистки синтезированного зонда с помощью нитроцеллюлозы.